Enhancing Smart and Adaptive Coastal Living: A Case from Pekalongan Regency - Aprilia Fitri Pamungkas; Iwan Rudiarto (The Journal of Indonesia Sustainable Development Planning, 2026)
This research analyzes the dimensions influencing the adaptation efforts of communities affected by tidal flooding toward the implementation of Smart and Adaptive Coastal Living in Pekalongan Regency. This study employs a scoring analysis with total of 12 (twelve) indicators from 4 (four) dimensions: infrastructure, connectivity and communication, economic diversification, and marine ecosystem protection. From the score calculations obtained, it is known that the most dominant dimension is economic diversification with an achievement index of 0.541, while the dimension with the lowest contribution is infrastructure with an achievement index of only 0.159. Regarding the achievements in the context of Smart and Adaptive Coastal Living, community adaptation tends to fall into the non-smart adaptive category because the available infrastructure is inadequate and the conditions of the community do not support the presence of smart innovations in the implementation of this concept. Among the twelve existing variables, the highest contributions to achievements at this level arise from the initiatives of coastal communities (K3) and alternative employment (AE). Both indicate a willingness to adapt to a living environment that continuously faces pressures resulting from flood disasters.